Pembuatan dan Penggunaan Alat Detektor Gempa Untuk Pendidikan Kebencanaan Bagi Anak Santri di Pondok Pesantren Al Muyamman, Giwangan, Yogyakarta - Rakhman, Arie Noor; Maulana, Fivry Wellda (LPPM IST AKPRIND Yogyakarta, 2022)
People who live in the Giwangan area, Umbulharjo District, Yogyakarta have public awareness in response to earthquake conditions. However, this is not the case for the migrant communities who lived after the earthquake in 2006. They are still inexperienced in dealing with earthquake situations. Some of them have not even interacted with local wisdom culture, especially in recognizing vibrations at the beginning of the earthquake. This is also the case in the neighborhood of education in Al Muyamman Giwangan. This community service aims to introduce ways of being responsive to the initial situation of the earthquake. The service method that has been carried out is through training in the manufacture and use of earthquake detectors for students. The results of the training showed that the participants were able to make an earthquake detector. This tool uses the sensitivity of the pendulum swing in a bottle against earthquake vibrations. Physically, the magnitude of the detected earthquake vibrations is like the ground surface vibration propagation when a truck is passed. Based on the approach to the magnitude of the Mercalli earthquake, the vibration is of magnitude 3 MMI (Modified Mercalli Intensity). This earthquake is equivalent to 4.3 on the Richter scale, still allowing people to save themselves. After the initial response to earthquake vibrations, it is necessary to be responsive when an earthquake occurs. This responsiveness is as understanding the existence of the assembly point location. We can carry evacuation efforts out if the location has exit access, release exits and supporting facilities that are in accordance with environmental conditions and local wisdom culture.